The Acoustic Change Complex in Response to Frequency Changes and Its Correlation to Cochlear Implant Speech Outcomes - McGuire, Kelli; Firestone, Gabrielle M.; Zhang, Nanhua; Zhang, Fawen (Frontiers in Human Neuroscience, 2021)
Abstract One of the biggest challenges that face cochlear implant (CI) users is the highly variable hearing outcomes of implantation across patients. Since speech perception requires the detection of various dynamic changes in acoustic features (eg., frequency, intensity, timing) in speech sounds, it is critical to examine the ability to detect the within-stimulus acoustic changes in CI users. The primary objective of this study was to examine the cortical auditory evoked potential (CAEP) to the within-stimulus frequency changes (F-changes), one type of the acoustic change complex (ACC), in adult CI users, and its correlation to speech outcomes. Twenty-one adult CI users (29 individual CI ears) were tested with psychoacoustic frequency change detection tasks, speech tests (Consonant Nucleus Consonant word recognition test or CNC, AzBio sentence recognition test in quiet and noise or AzBio-Q and AzBio-N, and the Digit-in-Noise or DIN test), and electroencephalographic (EEG) recordings. The stimuli for the psychoacoustic tests and EEG recordings were pure tones at 3 different base frequencies (0.25, 1, and 4 kHz) that contained a F-change at the midpoint of the tone. Results showed that the frequency change detection threshold (FCDT), ACC N1’ latency, and P2’ latency did not differ across frequencies (p>0.05). ACC N1’-P2 amplitude was significantly larger for 0.25 kHz than for other base frequencies (p<0.05). The mean N1’ latency across 3 base frequencies was negatively correlated with CNC word recognition (r = - 0.40, p < 0.05) and CNC phoneme (r = -0.40, p < 0.05), and positively correlated with mean FCDT (r = 0.46, p < 0.05). The P2’ latency was correlated with DIN (r = 0.47, p < 0.05) and mean FCDT (r = 0.47, p < 0.05). There was no statistically significant correlation between N1’-P2’ amplitude and speech outcomes (all ps > 0.05) Variability in CI speech outcomes assessed with the CNC, AzBio-Q, and DIN tests can be partially explained (approximately 16%-21%) by the variability of cortical sensory encoding of F-changes reflected by the ACC.